Let x and y be integers satisfying x 3 − y 2 = 1 1 .
Find the sum of all possible values of x satisfying this equation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Intriguing solution! @Worranat Pakornrat do you have any elementary solution?
In the 5th row, R H S is a congruence with S S S , S A S , A S A , R H A .
I would be somewhat surprised if there were an elementary way to solve this problem. I used MAGMA:
1 2 3 |
|
with output
1 2 3 |
|
Apparently this gives you all the integral points up to the sign of y . So the answer is 3 + 1 5 = 1 8 .
By the way, this particular curve has infinitely many rational points; MAGMA says it has rank 2 (and no nontrivial torsion).
Problem Loading...
Note Loading...
Set Loading...
First of all check the parity of an integral solution. Suppose that y is odd, this implies that x is even but
x 3 = y 2 + 1 1 x = 2 x ′ , y = 2 y ′ + 1
⟹ 8 x ′ 3 = 4 y ′ 2 + 4 y ′ + 1 2
2 x ′ 3 = y ′ ( y ′ + 1 ) + 3
But the L H S is even while the R H S is odd, so our assumption was false and a solution (if there exist any) must have odd x and even y
Now, since 1 1 is a Heegner number , we can exploit the fact that the ring Z [ 2 1 + 2 − 1 1 ] = { m + n ( 2 1 + 2 − 1 1 ) ∣ m , n ∈ Z } is a UFD
Factor the R H S
x 3 = ( y + − 1 1 ) ( y − − 1 1 )
We wish to prove that this two factors are coprime in the ring
Define the norm function as
N ( m + n d ) = m 2 − n 2 d
It's easy to prove that it has the property
α ∣ β ⟹ N ( α ) ∣ N ( β )
We are now going to consider a δ such that
δ ∣ y + − 1 1 δ ∣ y − − 1 1
It follows that
N ( δ ) ∣ y 2 + 1 1
And y 2 + 1 1 is odd so N ( δ ) must be odd too. In addition
δ ∣ ( y + − 1 1 ) − ( y − − 1 1 ) ≡ δ ∣ 2 − 1 1
We now know that N ( δ ) is odd and divides 4 4 , so it must be 1 1 or 1
If N ( δ ) = 1 1 then both x and y would be divisible by 1 1 , implying that
1 3 3 1 x ′ ′ 3 = 1 2 1 y ′ ′ 2 + 1 1
But v 1 1 ( L H S ) ≥ 3 while v 1 1 ( R H S ) = 1
Hence N ( δ ) = 1 and δ is a unit, so y + − 1 1 and y − − 1 1 are coprime
We have two coprime numbers whose product is a cube, so they must be two cubes themselves, up to some units
We can avoid the last restrinction noting that the units in the ring are ± 1 which are both cubes
Now what is left are some calculations and casework
y + − 1 1 = [ m + n ( 2 1 + 2 − 1 1 ) ] 3
8 y + 8 − 1 1 = [ 2 m + n ( 1 + − 1 1 ) ] 3
8 y + 8 − 1 1 = 8 m 3 + 1 2 m 2 n ( 1 + − 1 1 ) + 6 m n 2 ( 1 + − 1 1 ) 2 + n 3 ( 1 + − 1 1 ) 3
8 y + 8 − 1 1 = 8 m 3 + 1 2 m 2 n − 6 0 m n 2 − 3 2 n 3 + ( 1 2 m 2 n + 1 2 m n 2 − 8 n 3 ) − 1 1
Equating coefficients and simplifying
{ 2 y = 2 m 3 + 3 m 2 n − 1 5 m n 2 − 8 n 3 2 = 3 m 2 n + 3 m n 2 − 2 n 3
From the second equation we get that n ∣ 2 , so n = ± 1 , ± 2
n = 1 yelds no integer values for m
n = − 1 gives m = 0 or m = 1 , which yelds y = ± 4
n = 2 gives m = 1 or m = − 3 , which yelds y = ± 5 8
n = − 2 yelds no integer values for m
To conclude, the solutions to the equation are ( 3 ; ± 4 ) , ( 1 5 ; ± 5 8 ) and the sum of all the distinct values of x is 1 5 + 3 = 1 8